A Critical Review on Organizational Culture in Educational Settings - Salihu, Muftahu Jibirin (School of Social Sciences, 2015)
One of the most interesting fields or aspects of study among corporations, educational institutions, firms and businesses, whether it be small scale and large scale is the topic on organizational culture. In this research paper, the concept of organizational culture will be discussed in a greater detailed context. The researcher will basically be going into personal details on what he thinks is the organizational culture the organization where he belongs practices. In addition, this paper will be comparing and contrasting the functionalist and interpretive perspective of organizational culture. Moving beyond its definition, the researcher will also be taking the interpretive perspective and examine the interpretive perspective of organizational culture and its relevance in the organization where he belongs on top of the details on how that institution administers such perspective in its own organization. Particular examples will be provided by the researcher in this research paper based on his own personal experiences.